Escherichia coli Occurrence and Antimicrobial Resistance in a Swine Slaughtering Process - Sampaio, Aryele Nunes da Cruz Encide [UNESP]; Caron, Evelyn Fernanda Flores [UNESP]; Cerqueira-Cézar, Camila Koutsodontis [UNESP]; Juliano, Lára Cristina Bastos [UNESP]; Tadielo, Leonardo Ereno [UNESP]; Melo, Patrícia Regina Lopes [UNESP]; de Oliveira, Janaína Prieto [UNESP]; Pantoja, José Carlos de Figueiredo [UNESP]; Martins, Otávio Augusto [UNESP]; Nero, Luís Augusto; Possebon, Fábio Sossai [UNESP]; Pereira, Juliano Gonçalves [UNESP] (MDPI, 2024)
The swine production chain can be a reservoir of antimicrobial-resistant Escherichia coli, which transfers resistance genes to other bacteria, serving as an important biomarker in the One Health approach. This study aimed to identify the frequency and antimicrobial resistance profile of E. coli in the swine production chain, assess the presence of extended-spectrum beta-lactamases (ESBL), and compare resistance profiles across different sample types. A total of 622 samples of swine carcasses from various points of the slaughter process (n = 400), swine feces (n = 100), commercial cuts (n = 45), environment (n = 67), and feces from employees (n = 10) of a pig slaughterhouse certified by the Federal Inspection Service, located in São Paulo state, Brazil, were collected. A total of 1260 E. coli isolates were obtained from the samples, with 73.6% of the samples testing positive. The agar disk diffusion test was performed with 10 different classes of antimicrobials. To confirm the production of ESBLs, the isolates were submitted to a double-disk synergism test using cefotaxime, ceftazidime, and amoxicillin with clavulanic acid. Of the total isolates, 80.71% were multidrug resistant. All ESBL-producing isolates were multidrug resistant and resistant to amoxicillin, tetracycline, and chloramphenicol. Isolates from human feces samples had less chance of being multidrug resistant than samples from other sources. The diversity of resistance profiles was verified in the samples, not clustering according to the sources, except for human feces isolates that clustered, evidencing lower antimicrobial resistance variability of these samples. Antimicrobial resistance is significantly present in the pork production chain, necessitating a comprehensive multidisciplinary approach to effectively mitigate risks within the One Health framework.
Keywords: enterobacteria; ESBL; MDR; pigs